FORMULATION OF KONJAC GLUCOMANNAN AND CARRAGEENAN-BASED HARD CAPSULE (Jurnal Teknologi Industri Pertanian, 2026)
Commercial hard capsules are primarily manufactured from bovine or porcine gelatin, which often restricts consumer choice owing  to religious concerns and vegetarian lifestyles. Konjac glucomannan demonstrates superiority as a gelling and film-forming material, making it a highly potential gelatin substitute in the manufacture of hard capsules. This study employed response surface methodology (RSM) to design and determine the optimum conditions for a hard capsule formula based on konjac glucomannan and carrageenan. The independent variables analyzed were the ratios of konjac glucomannan (2.5%, 3%, and 3.5%; X1), carrageenan (1.5%, 2.0%, and 2.5%; X2), and glycerol (0, 0.125%, and 0.250%; X3). The dependent response variables analyzed were capsule moisture content and disintegration time. The moisture content ranged from 5.6% to 15.9%, indicating that higher ratios of konjac glucomannan and glycerol resulted in higher capsule moisture content. Capsule disintegration time ranged from 10.12 to 24.25 min, indicating that a higher glycerol ratio accelerated the hard capsule destruction time. Both the capsule moisture content and disintegration time were significantly influenced by the raw material used and the resulting capsule specifications.Keywords: carrageenan, formula optimization, hard capsule, konjac glucomannan